Perception Analysis of Social Network Tweets Using a Genetic Algorithm Based Approach (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2023)
We communicate, post different comments, communicating with different people in Social media. Different people of the world posted their views on COVID-19 during the pandemic. In this study we analysed the posted comments on social media. Analysis of the comment in social media is called sentiment analysis. We performed sentiment analysis on content from social media platforms, classifying it into either positive or negative categories. For this task, we proposed a different hybrid model. We used deep learning and genetic algorithm. GA algorithm and Stacked LSTM gave 95% positive sentiment. This model helps the health administrators in the world to make proper decisions to fight upcoming pandemic.